Water engineering : hydraulics, distribution, and treatment - Shammas, Nazih K.; Wang, Lawrence K. (Hoboken : Wiley, 2016)
'This book focus is on drinking water supply and treatment. Consequently, it devotes more depth to discussing water quality, quantity and pressure issues, problems related to emerging contaminants, water supply infrastructure, water treatment processes and water system selection'--
Includes bibliographical references and index.
Keywords: Waterworks; Drinking water